Transformation of Language, Literature, Regional Culture and Learning Society 5.0 Era - Nurjanah, Nunuy; Dingding Haerudin; Haris Santosa Nugraha (CV. Goresan Pena, 2023)
The existence of local languages continues to decrease the number of speakers, so it is necessary to carry out preventive efforts. The method can be in the form of transformation into digital form. This effort is a step to change the form or transfer print, audio, and video media into digital form. This paper aims to explain certain media that can be used as innovations in digital-based learning of the Sundanese language. The media are in the form of websites (sundanesepedia.com and sundaculture.com) and digital learning applications (MABS: Bahan Ajar Basa Sunda).